2020
DOI: 10.1002/er.5715
|View full text |Cite
|
Sign up to set email alerts
|

Preheatingstrategy ofvariable‐frequencypulse for lithium battery in cold weather

Abstract: Aiming to the issue of charging difficulty and capacity fading for lithium-ion battery at low temperature, this study proposes a preheating strategy using variablefrequency pulse. The innovation of this paper is to propose the thermo-electric coupling model based on the electrochemical impedance spectroscopy of battery at different temperatures, integrated with variable frequency changing for pulse method to develop an effective inner pre-heating strategy. Meanwhile, the evaluating method of impact of this str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…The comparative analysis found that mutual pulse heating not only consumes the least volume but also combines the advantages of internal uniform heating and no forced convection. Wu et al [57] proposed a thermoelectric coupling model based on electrochemical impedance spectra of batteries at different temperatures, combined with the pulse variable frequency method to formulate an effective internal preheating strategy, and developed a preheating strategy using frequency conversion pulses. The results show that the optimized frequency conversion pulse preheating strategy can heat the lithium-ion battery from −20 • C to 5 • C in 1000 s. At the same time, from the aspects of power consumption, capacity attenuation, internal resistance change, reduce the damage to the health of the battery, improve the performance of the battery in cold weather.…”
Section: Internal Heating Systemmentioning
confidence: 99%
“…The comparative analysis found that mutual pulse heating not only consumes the least volume but also combines the advantages of internal uniform heating and no forced convection. Wu et al [57] proposed a thermoelectric coupling model based on electrochemical impedance spectra of batteries at different temperatures, combined with the pulse variable frequency method to formulate an effective internal preheating strategy, and developed a preheating strategy using frequency conversion pulses. The results show that the optimized frequency conversion pulse preheating strategy can heat the lithium-ion battery from −20 • C to 5 • C in 1000 s. At the same time, from the aspects of power consumption, capacity attenuation, internal resistance change, reduce the damage to the health of the battery, improve the performance of the battery in cold weather.…”
Section: Internal Heating Systemmentioning
confidence: 99%
“…The pulse preheating method uses pulse current to generate heat through the internal impedance of the cell to preheat the batteries. Compared with air preheating, the pulse preheating method can achieve a more uniform distribution of heat generation inside the battery pack, and a low‐temperature variance is beneficial to battery health 152 . An effective preheating strategy is developed using a thermo‐electric coupling model based on the EIS of the cell and the pulse frequency is varied between 1000 and 3637.1 Hz to compare their preheating effect.…”
Section: Application Of Btms In Evsmentioning
confidence: 99%
“…Compared with air preheating, the pulse preheating method can achieve a more uniform distribution of heat generation inside the battery pack, and a low-temperature variance is beneficial to battery health. 152 An effective preheating strategy is developed using a thermo-electric coupling model based on the EIS of the cell and the pulse frequency is varied between 1000 and 3637.1 Hz to compare their preheating effect. The optimal pulse configuration (the 2637.5 Hz frequency) can heat the cell from À20 C to 5 C within 1000 seconds.…”
Section: Internal Heatingmentioning
confidence: 99%